PENGARUH PENGGUNAAN MIND MAPPING PADA PEMBELAJARAN TEMATIK TERHADAP PEMAHAMAN KONSEP SISWA KELAS IV SD NEGERI 064987 MEDAN - Wilda Febriyanti Panjaitan; Sutarini Sutarini (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the effect of the mind mapping method on the conceptual understanding of fourth grade students at SD Negeri 064987 Medan. This type of research is a quasi experiment using a nonequivalent control group design. This research was conducted at SD Negeri 064987 Medan with the research subjects being students of class IVA and IVB, totaling 54 students. This study consists of the dependent variable, namely conceptual understanding and the independent variable, namely the mind mapping method. Data collection techniques and instruments used in research are tests. The data analysis technique used was a hypothesis test with a t-test to see differences in understanding the concept of the experimental group and the control group with a significant level of 5%. The results of this study indicate that there is an influence of the mind mapping method on the understanding of the concepts of fourth grade students at SD Negeri 064987 Medan. This influence is proven by the results of the t-test in the posttest of the experimental group and the control group, namely sig 0.014 <0.05 and tcount 2.548 > ttable 2.006. So, it can be concluded that there are differences in conceptual understanding between students who are taught by the mind mapping method and students who are taught by conventional methods